Bibliometric Insights into Metacognitive Scaffolding: A Review of Research in Educational Psychology - Judijanto, Loso (Eastasouth Institute, 2025)
This study presents a comprehensive bibliometric analysis of research on metacognitive scaffolding within the domain of educational psychology, aiming to uncover the intellectual structure, thematic patterns, and emerging trends in the field. Drawing data from the Scopus database covering publications from 2000 to 2025, the study analyzed 453 documents using VOSviewer software to perform co-citation, co-authorship, keyword co-occurrence, and temporal trend analyses. The results highlight the dominance of foundational theorists such as Flavell, Vygotsky, and Zimmerman, alongside contemporary scholars like Azevedo who have advanced the integration of metacognitive scaffolding into digital learning environments. Keyword analysis reveals core themes related to metacognition, scaffolding, and computer-aided instruction, as well as emerging areas such as inquiry learning, cognitive load, game-based learning, and learning analytics. The United States emerged as the most influential country in collaborative research networks, while regions like Indonesia remain underrepresented. These findings indicate a mature yet dynamically evolving research field that is increasingly shaped by technological innovation and interdisciplinary approaches. The study offers valuable insights for scholars, educators, and policymakers aiming to design effective, context-sensitive, and ethically grounded metacognitive scaffolding interventions in both traditional and digital learning settings.